HOW TO COPE WITH BABY BLUES: A CASE REPORT - Herdian Fitria Widyanto Putri; Frilya Rachma Putri (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2022)
During parturition phase, usually mother cannot get through psychological adaptations well, it can cause something that you might not accept-postpartum mental disorders called baby blues.Â There are 30-75% of women after childbirth who experience the baby blues. Many factors affect baby blues. The symptoms that begin within a few days of delivery include mood lability, irritability, tearfulness, generalized anxiety, sleep, and appetite disturbance. The author reported a case of women with baby blues. The instrument uses Edinburgh Postnatal Depression Scale (EPDS) for screening. EPDS test on the patient showed a score of 13. The patient gets treatment with classical music therapy, a support system, and continued breastfeeding. After treatment, the patient can control her emotions, sleep well, and already breastfeed the baby. The husband also takes a role in caring for their baby. EPDS test on the patient showed a score of 8. Early detection and appropriate treatment from a midwife can decrease baby blues symptoms.Â Keywords: post-partum mental disorder, baby blues, EPDS.